Interleukin(IL)-36α and IL-36γ Induce Proinflammatory Mediators from Human Colonic Subepithelial Myofibroblasts - Kanda, Toshihiro; Nishida, Atsushi; Takahashi, Kenichiro; Hidaka, Kentaro; Imaeda, Hirotsugu; Inatomi, Osamu; Bamba, Shigeki; Sugimoto, Mitsushige; Andoh, Akira (Frontiers in Medicine, 2015)
Background: Interleukin (IL)-36 cytokines are recently reported member of the IL-1 cytokine family. However, there is little information regarding the association between IL-36 cytokines and gut inflammation. In the present study, we investigated the biological activity of IL-36α and IL-36γ using human colonic subepithelial myofibroblasts (SEMFs). Methods: The mRNA expression and the protein expression of target molecules in SEMFs were evaluated using real-time PCR and enzyme-linked immunosorbent assay (ELISA), respectively. The intracellular signaling of IL-36 cytokines was analyzed using Western blot analysis and small interfering RNAs (siRNAs) specific for MyD88 adaptor proteins (MyD88 and IRAK1) and NF-κB p65. Results: IL-36α and IL-36γ significantly enhanced the secretion of IL-6 and CXC chemokines (CXCL1, CXCL2, and CXCL8) by SEMFs. The combination of IL-36α/γ and IL-17A or of IL-36α/γ and tumor necrosis factor (TNF)-α showed a synergistic effect on the induction of IL-6 and CXC chemokines. The mRNA expression of proinflammatory mediators induced by IL-36α and/or IL-36γ was significantly suppressed by transfection of siRNA for MyD88 or IRAK1. Both inhibitors of mitogen activated protein kinases (MAPKs) and siRNAs specific for NF-κBp65 significantly reduced the expression of IL-6 and CXC chemokines induced by IL-36α and/or IL-36γ. Conclusion: These results suggest that IL-36α and IL-36γ contribute to gut inflammation through the induction of proinflammatory mediators.